Lima festeja a la Inmaculada (1656): texto criollo y poderes urbanos - Latasa, Pilar (2017)
Analysis of the festivities of the Immaculate Conception celebrated in Lima in 1656, from the account written by Diego de León Pinelo Gutiérrez. This Creole text reinterprets in baroque terms the cult of the Immaculate Conception in the City of Kings. Through it we can study these lengthy festivals, which involved the participation of the city’s most important institutions and corporate bodies, mobilizing considerable resources and people. Thus, the text is conceived as a political and religious exaltation of the city of Lima, typical of the festive genre and of the chorographic literature, which also connects with the emerging Creole discourse.